MOBILISASI SUARA: PENGARUH AGAMA DALAM PRAKTIK VOTE BUYING DI PILKADA (STUDI DI KABUPATEN BONE BOLANGO) - Yasin, Hendra (Farabi, 2024)
Vote buying or buying and selling of votes is one of the phenomena of election violations that is increasingly characterizing electoral democracy in Indonesia. Even though this practice which harms the democratic system is widely opposed, it does not necessarily mean that vote buying disappears from general election polemics in this country. This research, which uses survey method, will reveal the results of vote mobilization through the practice of vote buying in society and whether religious moral values ​​have a significant role in influencing the results of voter decisions, especially in Regional Elections (Pilkada) in Bone Regency. Bolango. The quantitative data for this research were obtained from the results of a survey with a number of respondents who were interviewed using a list of questionnaires that had been compiled systematically, the results of which were then combined using a qualitative approach using James Scott's patron-client theory. The results of this research show that the majority of Bone Bolango residents understand the illegal practice of vote buying, but this does not necessarily mean that this practice is rejected in general elections in the area. Regional socio-economic conditions also seem to play an important role in people's decisions in accepting or rejecting existing money politics practices. However, the religious values ​​inherent in individuals are in fact unable to influence society to reject the invitation to vote buying. Keywords: vote buying, electoral democracy, regional elections